2017
DOI: 10.1007/s11695-017-2738-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Bariatric Surgery in Morbidly Obese Adolescents: a Systematic Review and Meta-Analysis of 950 Patients with a Minimum of 3 years Follow-Up

Abstract: Although bariatric surgery is a safe and effective procedure in the treatment of adolescent morbid obesity, long-term data is scarce regarding its nutritional and developmental complication in this growing population of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 35 publications
1
41
0
4
Order By: Relevance
“…40 In nonsyndromic paediatric populations, recent systematic reviews showed that significant and durable weight loss results could be achieved for up to 7 years. 10 Comparing with the other literature data that reported the 5-year outcomes of bariatric surgery on PWS patients, the weight loss outcomes of our patient cohort were slightly more inferior (Table 4).…”
Section: Revisional Surgerysupporting
confidence: 39%
See 1 more Smart Citation
“…40 In nonsyndromic paediatric populations, recent systematic reviews showed that significant and durable weight loss results could be achieved for up to 7 years. 10 Comparing with the other literature data that reported the 5-year outcomes of bariatric surgery on PWS patients, the weight loss outcomes of our patient cohort were slightly more inferior (Table 4).…”
Section: Revisional Surgerysupporting
confidence: 39%
“…8,9 To treat nonsyndromic childhood and adolescent obesity, bariatric surgery has been increasingly advocated due to its favourable weight loss outcomes similar to adults. 10 As for PWS, while the contemporary bariatric operations are regarded as safe procedures, the efficacy of bariatric surgery on weight loss and comorbidity resolution was largely inconsistent. Long-term follow-up data were particularly lacking.…”
mentioning
confidence: 99%
“…At 36 months, significant weight loss was maintained with a mean BMI reduction of 10.3% in patients who underwent LAGB, 13% in patients who underwent VSG, and 15% in patients who underwent RYGB. 26,27 More recently, an analysis of electronic health record data compared the effectiveness of bariatric procedures among pediatric patients and demonstrated a similar BMI reduction among patients who received VSG or RYGB, and a lower BMI reduction in patients who received LAGB. 28 Complications Surgical complications are infrequent, with the majority being defined as minor (15%) and occurring in the early postoperative period (eg, postoperative nausea and dehydration).…”
Section: Outcomes On Weight Loss and Comorbidity Resolutionmentioning
confidence: 99%
“…28 Complications Surgical complications are infrequent, with the majority being defined as minor (15%) and occurring in the early postoperative period (eg, postoperative nausea and dehydration). 11,16,27 Major perioperative complications (30 days) were reported in 8% of Teen-LABS participants. In addition, 2.7% required reoperation before hospital discharge, which was similar to adults.…”
Section: Outcomes On Weight Loss and Comorbidity Resolutionmentioning
confidence: 99%
“…The guidelines call for frequent and comprehensive labs that can equate to significant costs. While bariatric surgical procedures are able to effectively reduce the amount of caloric consumption through anatomic and physiologic alteration, nutritional deficiency can be an additional unintended result [1,2]. To remedy the latter, patients are prescribed nutritional supplements and undergo a series of follow-up blood tests following bariatric surgery to detect potential nutritional deficiencies.…”
mentioning
confidence: 99%